2005
DOI: 10.1111/j.1365-2664.2004.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide levels and arbuscular mycorrhizal fungi in golf putting greens

Abstract: Summary1. Annual meadow grass Poa annua is the most problematic weed within sports turf in temperate climates. It is so abundant that herbicides cannot be used against it because almost total loss of the sward would occur. Arbuscular mycorrhizal (AM) fungi can be used as biological control agents of P. annua , acting to reduce its growth while increasing that of desirable perennial grasses. However, natural levels of AM fungi in amenity turf are very low. Sports turf is characterized by high fungicide usage, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…This phylum, as well as the total number of mycorrhizae genera, was highest on the putting greens of the organic course and tended to be higher on the conventional putting greens, although not statistically. Bary et al (2005) found higher numbers of these organisms on putting greens, in contrast with past studies, and speculated that potentially they had developed resistance to fungicides or that fungicides never reached them in the soil. This could be true for our study, where the additional fungicides did not affect the mycorrhizae.…”
Section: Discussioncontrasting
confidence: 85%
“…This phylum, as well as the total number of mycorrhizae genera, was highest on the putting greens of the organic course and tended to be higher on the conventional putting greens, although not statistically. Bary et al (2005) found higher numbers of these organisms on putting greens, in contrast with past studies, and speculated that potentially they had developed resistance to fungicides or that fungicides never reached them in the soil. This could be true for our study, where the additional fungicides did not affect the mycorrhizae.…”
Section: Discussioncontrasting
confidence: 85%
“…2 and 3). The exposure concentration of 0.3 mg/ L can be compared with levels of 0.1 to 1.4 mg fenarimol/kg soil found on putting greens in southeastern England [36]. Ecdysteroid levels in male M. affinis have been observed to increase during male sexual maturation (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to have no effect on arbuscular mycorrhizal (AM) colonization in Poa pratensis growing on golf greens (Bary et al 2005). Application of fungicide is to the leaves in a dense grassland, so little is likely to reach the soil, and fenarimol has also been shown to have low toxicity to earthworms (Leslie 1994).…”
Section: Identity Effectsmentioning
confidence: 99%